Potential use of byproducts from cultivation and processing of sweet potatoes - Akoetey,Winifred (2017)
ABSTRACT: The cultivation and processing of sweet potatoes into a variety of products yields both solid and liquid organic waste. Solid waste includes peelings and trimmings from the sweet potato root and sweet potato leaves and vines. Liquid waste results from various processing methods and creates significant amounts of nutrient rich waste water. Sweet potato waste materials contain carbohydrates, proteins, phenolic compounds, macro and micro nutrients, and pigments that have the potential of being extracted or utilized for various downstream processes and products. This review examines many of the different ways that these waste products can be utilized.